Stinging larvae (Lepidoptera) in backyard crops in Volcán, Chiriquí, Panama - Collantes, Ruben (2022)
The objective of the study was to identify the stinging larvae of the Order Lepidoptera, found in backyard crops in Volcán, Chiriquí Province, Panama (8°46’ N 82°38’ W, 1378 m a. s. l.). For this, five random trips were carried out, checking the soil, wild vegetation, fruit crops and ornamental plants. The larvae were photographed and identified with the support of specialized literature. According to the results, four species of Lepidoptera stinging larvae were identified, corresponding to Acharia stimulea (Clemens, 1860) (Limacodidae) in heliconias, Phobetron hipparchia (Cramer, 1777) (Limacodidae) in mango and loquat, Megalopyge opercularis (Smith, 1797) (Megalopygidae) on hibiscus and Automeris metzli (Salle, 1853) (Saturniidae) on the soil. These results are close to what was found in a research previously carried out on horticultural crops in Cerro Punta; where the families Limacodidae, Megalopygidae and Saturniidae were also represented by four species, being M. opercularis and A. stimulea the ones that coincided in both locations. In conclusion, four species of stinging larvae of the Order Lepidoptera were identified, associated with backyard crops in Volcán, Chiriquí; which can potentially cause erucism in people. It is recommended to make more disclosure on the matter, to prevent possible effects on health.